জ্ঞানতাপস আব্দুর রাজ্জাক স্মারকগ্রন্থ - রাজ্জাক, আব্দুর, ১৯১৪-১৯৯৯; আনিসুজ্জামান
Contributed articles on the life and works of Ābdura Rājjāka, 1914-1999, college teacher, educator and political activist from Bangladesh; commemoration volume.